Personal distress and the influence of bystanders on responding to an emergency - Hortensius, Ruud (Springer US, 2016)
Spontaneous helping behavior during an emergency is influenced by the personality of the onlooker and by social situational factors such as the presence of bystanders. Here, we sought to determine the influences of sympathy, an other-oriented response, and personal distress, a self-oriented response, on the effect of bystanders during an emergency. In four experiments, we investigated whether trait levels of sympathy and personal distress predicted responses to an emergency in the presence of bystanders by using behavioral measures and single-pulse transcranial magnetic stimulation. Sympathy and personal distress were expected to be associated with faster responses to an emergency without bystanders present, but only personal distress would predict slower responses to an emergency with bystanders present. The results of a cued reaction time task showed that people who reported higher levels of personal distress and sympathy responded faster to an emergency without bystanders (Exp. 1). In contrast to our predictions, perspective taking but not personal distress was associated with slower reaction times as the number of bystanders increased during an emergency (Exp. 2). However, the decrease in motor corticospinal excitability, a direct physiological measure of action preparation, with the increase in the number of bystanders was solely predicted by personal distress (Exp. 3). Incorporating cognitive load manipulations during the observation of an emergency suggested that personal distress is linked to an effect of bystanders on reflexive responding to an emergency (Exp. 4). Taken together, these results indicate that the presence of bystanders during an emergency reduces action preparation in people with a disposition to experience personal distress.